2007
DOI: 10.1111/j.1464-5491.2007.02109.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in thioredoxin interacting protein (TXNIP) is associated with hypertriglyceridaemia and blood pressure in diabetes mellitus

Abstract: This is the first report to implicate TXNIP in a human disorder of energy metabolism, Type 2 diabetes. The effect of TXNIP on triglycerides is influenced by plasma glucose concentrations, suggesting that the biological relevance of TXNIP variations may be particularly relevant in recurrent episodes of hyperglycaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…Evidence for a connection between TXNIP and metabolic disease was revealed through a genome wide study that reported high expression of TXNIP in pre‐diabetic and diabetic patient muscle biopsies . Subsequently, specific TXNIP variants have been associated with hyperglycemia and high triglyceride levels in diabetes patients . Correlating with this data, high glucose induces TXNIP expression in numerous cell types associated with metabolic disease (e.g., adipocytes, skeletal myocytes, and β‐cells), and conversely, insulin can repress TXNIP expression .…”
Section: Nlrp3 In Health and Diseasementioning
confidence: 97%
“…Evidence for a connection between TXNIP and metabolic disease was revealed through a genome wide study that reported high expression of TXNIP in pre‐diabetic and diabetic patient muscle biopsies . Subsequently, specific TXNIP variants have been associated with hyperglycemia and high triglyceride levels in diabetes patients . Correlating with this data, high glucose induces TXNIP expression in numerous cell types associated with metabolic disease (e.g., adipocytes, skeletal myocytes, and β‐cells), and conversely, insulin can repress TXNIP expression .…”
Section: Nlrp3 In Health and Diseasementioning
confidence: 97%
“…Recent studies suggested that Txnip expression is increased in skeletal muscle of human T2DM and impaired glucose tolerance (IGT) patients (59, 60). It was also reported that a genetic variation of the Txnip gene is associated with hypertriglyceridemia and increased diastolic blood pressure (61). Interestingly, Txnip expression is induced by high glucose conditions, while it is reduced by insulin (59).…”
Section: Thioredoxin1/txnip Redoxisome Critical For Pathogenesis Ofmentioning
confidence: 99%
“…TXNIP expression is elevated in the vasculature and the pancreas (Minn et al, 2005) of diabetic animals and in the skeletal muscle of human type 2 diabetes (Parikh et al, 2007). Genetic variation in TXNIP is associated with hypertriglyceridemia and blood pressure in human type 2 diabetes mellitus (van Greevenbroek et al, 2007). …”
Section: Thioredoxin-interacting Protein (Txnip) Is a Metabolic Contrmentioning
confidence: 99%